Which dynamic pricing rule is most preferred by consumers? Application of choice experiment - Yumi Yoshida; Kenta Tanaka; Shunsuke Managi (Journal of Economic Structures, 2017)
This study investigates consumers' preference for dynamic pricing rules using a choice experiment. Among alternative electricity pricing rules, time of use (TOU) is most preferred by consumers, and our estimation results show that TOU has the highest value of WTP among pricing rules. Furthermore, consumers' characteristics affect their choice of a pricing rule. Our results show that risk preference in particular affects the choice probability of each pricing rule.
Keywords: 330; Choice experiment; Dynamic pricing; Electricity